2010
DOI: 10.1080/1550428x.2010.511085
|View full text |Cite
|
Sign up to set email alerts
|

Victimization, Family Rejection, and Outcomes of Gay, Lesbian, and Bisexual Young People: The Role of Negative GLB Identity

Abstract: Victimization and family rejection of sexual orientation are two salient stressors facing gay, lesbian, and bisexual (GLB) young people. While initial research has established a link between these sexuality-related stressors and GLB youths' mental health outcomes, the factors that underlie this relationship remain unclear. The current study examines the role of negative GLB identity (i.e., negative feelings about one's own sexual orientation) in mediating the relationship between sexuality-related stress (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 36 publications
6
56
0
2
Order By: Relevance
“…Such internalization of negative thoughts and feelings associated with being gay or lesbian are indicative of internalized heterosexism. This finding is consistent with past research which has linked negative family responses to internalized heterosexism, weakened identity, and lower self- A c c e p t e d M a n u s c r i p t 32 esteem (Berenson et al, 2005;Bregman et al, 2013;Pachankis et al, 2008;Willoughby et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Such internalization of negative thoughts and feelings associated with being gay or lesbian are indicative of internalized heterosexism. This finding is consistent with past research which has linked negative family responses to internalized heterosexism, weakened identity, and lower self- A c c e p t e d M a n u s c r i p t 32 esteem (Berenson et al, 2005;Bregman et al, 2013;Pachankis et al, 2008;Willoughby et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Some were negatively affected to such a degree that they thought of suicide, with several having attempted it. This impact is well documented in other studies which have demonstrated the association between family rejection and depression, increased drug and alcohol use, risky sexual behavior, suicidal ideation and suicidal attempts (e.g., D'Augelli et al, 1998;Darby-Mullins & Murdock, 2007;Morano, Cisler, & Lemerond, 1993;Proctor & Groze, 1994;Rothman et al, 2012;Ryan et al, 2009;Willoughby et al, 2010).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Consistent with minority stress theory (Meyer, 2003), the unique stress associated with having a stigmatized sexual minority status is thought to be a significant factor contributing to health disparities among LGB individuals in the United States (Institute of Medicine, 2011; Lehavot & Simoni, 2011;Lick et al, 2013). For example, sexual identity disclosure can result in negative reactions and rejection by family members and important others (e.g., Savin-Williams & Ream, 2003), and such rejection is associated with identity difficulties (Bregman, Malik, Page, Makynen, & Lindahl, 2013;Willoughby, Doty, & Malik, 2010), depression and anxiety (Puckett, Woodward, Mereish, & Pantalone, 2014;Willoughby et al, 2010), increased substance use (Rosario, Schrimshaw, & Hunter, 2009), and other negative health outcomes (Ryan, Huebner, Diaz, & Sanchez, 2009). Loss of family and other support as a result of sexual identity disclosure (Bregman et al, 2013;Savin-Williams & Ream, 2003) is likely to elevate stress levels, whereas connection to and acculturation within the gay community may have a buffering effect against stress (e.g., Condit, Kitaji, Drabble, & Trocki, 2011;Rosario, 2008).…”
Section: Stigma Microaggressions and Stress As Related To Risk Behamentioning
confidence: 99%
“…En l'occurrence, l'homophobie intériorisée, définie comme l'intériorisation des violences homophobes, de l'hétérosexisme et des sentiments négatifs à l'endroit de soi et de son orientation sexuelle (Herek, 2004), constitue une forme de stress proximal qui peut compromettre la capacité d'adaptation d'une personne (Meyer, 2003 ;Hatzenbuehler, 2009). Lorsqu'ils doivent faire face à la stigmatisation de leur orientation sexuelle, les JMS présentent en effet des difficultés d'acceptation d'eux-mêmes qui se manifestent notamment par de l'homophobie intériorisée et une faible estime d'eux-mêmes (Blais et al, 2013 ;Willoughby, Doty et Malik, 2010), lesquelles sont associées à une moindre utilisation des ressources sociales et psychologiques ainsi qu'à la détresse psychologique (Lehavot et Simoni, 2011 ;Szymanski et Kashubeck-West, 2008). Considérant que l'intégration harmonieuse d'une orientation sexuelle minoritaire est cruciale pour la santé mentale des jeunes de minorités sexuelles (Chamberland et al, 2011 ;Rosario et al, 2011 ;Luhtanen, 2002), il est important d'identifier les variables susceptibles d'influencer l'impact des agents stressants distaux et proximaux sur la santé mentale des JMS.…”
Section: Introductionunclassified